A Fractured Rock Geophysical Toolbox Method Selection Tool. Issue 3 (6th January 2016) - Day‐Lewis, F.D.; Johnson, C.D.; Slater, L.D.; Robinson, J.L.; Williams, J.H.; Boyden, C.L.; Werkema, D.; Lane, J.W.
Abstract : Article impact statement : A spreadsheet‐based software is presented to identify methods for use at fractured‐rock sites, based on project goals and site description.